PENGGUNAAN SUMUR RESAPAN UNTUK MENGURANGI GENANGAN AIR HUJAN DI KAMPUS KARANGMALANG UNIVERSITAS NEGERI YOGYAKARTA - Didik Purwantoro, Lutjito, Sudiyono AD (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The objectives of this studywas to solve the problem of floodwater due to the rainwater runoff and to reduce the flow rate of the runoff at the Colombo Street in front of the Faculty of Sport Science, Yogyakarta State University (YSU). This study was conducted based on the existing primary and secondary data. The data analysis to get the rainfall intensity was conducted using the analytical method that obtain the values of the standard deviation, the mean, the coefficient of variation, the asymmetry and kurtosis. From these values, it was obtained the types of eligible distribution after going through the test to get the maximum rainfall in the period of 2 years, 5 years, 10 years, 20 years and 25 years. Based on the data, the arch intensity was examined. The analysis showed if20% of YSU area is occupied by infiltration wells or if there are 250 infiltration wells in which 1 infiltration well is used for the area of 350 m2, the need of infiltration wells will be covered and it is going to reduce the flow rate of the runoff in 0.552 m3/s. This is consistent with the concept of sustainable rainwater drainage system based on the conservation of ground Water. Essentially,it is a drainage system in which the rainwater falling on the roof/pavement, is accommodated in a system of water absorption among others infiltration Wells therefore it will reduce the the floodwater runoff at the Colombo street. Another benefit isthe infiltration wells will also increase the ground water level. Keywords: Rate of Flow, Infiltration Well, Rain Water